MODELS OF BASIC ELECTROMAGNETIC WAVES IN THE BI-ISOTROPIC MEDIUM WITH SPACE DISPERSION - V. T. Erofeenko (Informatika)
A mathematical models describing the propagation of monochromatic electromagnetic waves in the biisotropic medium with space dispersion is being developed. Modeling is based on the transformation of integro-differential equations for bi-isotropic medium to the differential equations electrodynamics, containing electrical and magnetic polarizations in operator form with differential Laplace operator. Within the developed model it is analytically constructed a full system of basic plane, spherical and cylindrical electromagnetic fields extending in the homogeneous bi-isotropic medium with space dispersion.